Improving Students’ Speaking Skill Through Cooperative Role Play - Prasetya, Eska Perdana; Asrudin, Muhammad (ENGLISH JOURNAL, 2016)
Language is one of the ways people use to communicate each other. In this globalization era, people should be able to understand some foreign languages, especially English. It has been stated as an international language. According to Patel and Jain (2008:6) “English is the language of the world.” The writer points out that English is one of the important languages that is used as the international language on many interrelationships with the various aspects of life in the world. Therefore, English is used by people in order they are able to communicate each other from the different countries in the world. In Indonesia, English is set as the first foreign language and it becomes one of compulsory subject that is formally taught by students from Junior High School to Senior High School and University.